Evaluation of an assessment system for professionalism amongst dental students. (21st July 2016) - Zijlstra‐Shaw, S.; Roberts, T.; Robinson, P. G
Abstract: Introduction: Dental professionalism is an essential requirement to practice dentistry that covers both abilities and personal qualities. Therefore, a programme of assessment that promotes personal and professional development throughout the undergraduate dental education course is needed. This study aimed to develop and validate a system to assess dental students' professionalism based on a previously developed conceptual framework. Methods: Using the framework, an assessment programme was designed to encourage students to reflect on and explain their observed behaviours with appropriate feedback. The programme was panel‐tested and then administered to a cohort of senior dental students. Internal reliability criterion validity and construct validity were evaluated quantitatively, whilst the usefulness of the programme was evaluated qualitatively. Results: Mean of student, staff and agreed grades was similar, and there were no floor or ceiling effects. All item‐total correlations were >0.6 and Cronbach's alpha = 0.95 indicating acceptable internal reliability. All items correlated significantly with global ratings indicating good criterion validity. All hypothesized correlations were significant, and grades were not related to age or gender. Qualitative data produced three themes: assessment process, educational value and suggestions for improvement. Conclusion: The assessment programme has good internal reliability and validity and suggests that basing an assessment system around the explicit theoretical model is a valuable educational tool.